The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.pharmthera.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the mevalonate cascade as a new therapeutic approach in heart disease, cancer and pulmonary disease

Abstract: The cholesterol biosynthesis pathway, also known as the mevalonate (MVA) pathway, is an essential cellular pathway that is involved in diverse cell functions. The enzyme 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase (HMGCR) is the rate-limiting step in cholesterol biosynthesis and catalyzes the conversion of HMG-CoA to MVA. Given its role in cholesterol and isoprenoid biosynthesis, the regulation of HMGCR has been intensely investigated. Because all cells require a steady supply of MVA, both the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 398 publications
(443 reference statements)
3
129
0
2
Order By: Relevance
“…Accordingly, simvastatin treatment restored doxorubicin sensitivity to the level of the parental cell line. Mevalonate pathway overactivation is a frequent event in carcinogenesis [20][21][22], and the rate-limiting enzyme of the pathway, 3-hydroxy 3-methylglutaryl coenzyme A reductase (HMGCR), has been even classified as a metabolic oncogene [28]. The consequences of mevalonate pathway activation can be relevant not only for cancer development per se, but also for therapy response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, simvastatin treatment restored doxorubicin sensitivity to the level of the parental cell line. Mevalonate pathway overactivation is a frequent event in carcinogenesis [20][21][22], and the rate-limiting enzyme of the pathway, 3-hydroxy 3-methylglutaryl coenzyme A reductase (HMGCR), has been even classified as a metabolic oncogene [28]. The consequences of mevalonate pathway activation can be relevant not only for cancer development per se, but also for therapy response.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of mevalonate pathway activation can be relevant not only for cancer development per se, but also for therapy response. Several mechanisms may contribute, reflecting different outputs of the pathway [20][21][22]. One of these is isoprenylation of Ras, Rac and Rho oncoproteins, which is crucial for their membrane localization and subsequent signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins reduce cholesterol biosynthesis by inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and in addition have pleiotropic immunomodulatory effects that may be of value for the treatment of chronic inflammatory diseases [144,145]. Preclinical in vitro and in vivo studies, including experimental models of allergic [146] and tobacco-smokeinduced lung inflammation [147] found that statins reduce components of airway inflammation potentially relevant to the pathogenesis of asthma and smoke-induced airway diseases.…”
Section: Statinsmentioning
confidence: 99%
“…All statins inhibit within the liver conversion of HMG-CoA to mevalonate, a cholesterol precursor. 6 This process takes place in hepatocytes and the degree of hepatic HMG-CoA reductase inhibition predetermines the extent of the cholesterol-lowering effect of statins. 7 Inhibition of HMG-CoA reductase in extrahepatic cells and tissues is unlikely to affect lipid homeostasis and serum lipid level.…”
Section: Introductionmentioning
confidence: 99%